Resource Ownership and Human Interaction : A Theoretical Exposition - Marothia, Dinesh (Annals of Arid Zone, 2016)
This review paper focuses socio-economic and environmental aspects of natural resource problem within the context of an interdependent network emphasizing human interactions with respect to natural resource use. It also traces the ambiguities and inadequacies in theoretical approaches with respect to the components of natural resource problems (i.e. rights, power, freedom. security. interest conflicts and interdependence) and proposes a theoretical formulation for drawing logical inferences in natural resource policy.